The journalist’s attitude on the editorial “The mothers whose children are held hostage by Hamas” - Cahyono, Setyo Prasiyanto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study explores the use of attitude appraisal in revealing the mothers’ emotions and feelings regarding their attitude toward the situation in which their children are held hostage by Hamas. The study employs a qualitative method to describe the language phenomenon expressed by the journalist in describing the mothers’ attitudes. The data were obtained from the Guardian online newspaper published in 2023, and the samples were selected purposively. Content analysis was used to examine the data, employing Martin and White’s (2005) appraisal framework to classify the data.  This study focuses on one type of appraisal, namely attitude, which covers affect, judgment, and appreciation. The findings of this study reveal that the journalist tends to defend Israel and oppose Hamas. It is seen through positive attitudes, which are dominantly produced by the journalist in expressing his arguments. Besides that, the journalist gives his positive evaluation of the situation that occurred in Gaza and Israel explicitly and implicitly. He exploits negative affect to show his concern and unhappiness to see the three children of Israel who were held hostage by Hamas. In addition, the genre of the editorial is media discussion since it discusses issues of Israeli children's kidnapping.